Penguatan Sinergi Peran Perguruan Tinggi dalam Upaya Mempercepat Pembanguan dan Peningkatan Kesejahteraan Masyarakat Kecamatan Kademangan - Nining Haryuni; Nevy Norma Renityas; Bima Tangguh Alam; Arif Fuadi; Iryana Puruhitasari; Eka Zahra Puspitasari; Chairumin Alfin; Ilham Effendy; Erwin Endriawan; Dita Novarina Gunawati (Universitas Madani Indonesia, 2025)
This community service activity was held to strengthen the role of Higher Education in efforts to accelerate development and improve the welfare of the people of Kademangan District. This activity was carried out in November 2024 at the Kademangan District Office, Blitar Regency, located at Jl. Raya Trisula No. 44, Suruhwadang, Kademangan, Blitar, East Java, Indonesia. The approach method used was socialization with lectures and discussions. The activity was carried out in 3 stages including the planning, implementation and evaluation stages. The evaluation of this activity found that as many as 8 villages out of 14 villages in Kademangan District decided to collaborate with academic staff from the community service team to help make development in the village a success. These villages include Plosorejo, Rejowinangun, Plumpungrejo, Sumberjo, Jimbe, Darungan, Sumberjati and Dawuhan. This collaboration is related to the development of BUMDES, improving the quality of human resources, village spatial planning, development of the livestock sector which is the majority of the community's livelihood and a data security system using information technology. The implementation of this PkM activity can be concluded to be able to strengthen the synergy of the role of Higher Education in efforts to accelerate development and improve the welfare of the Kademangan District community.